Does the cerebellum intervene in the abnormal somatosensory temporal discrimination in Parkinson's disease?. Issue 7 (July 2015) - Di Biasio, F.; Conte, A.; Bologna, M.; Iezzi, E.; Rocchi, L.; Modugno, N.; Berardelli, A.
Abstract Introduction somatosensory temporal discrimination threshold (STDT) measures the ability to perceive two stimuli as being sequential. Altered STDT has been reported in Parkinson's disease (PD). The cerebellum seems to play a role in the pathophysiology of PD, and may consequently be involved in the pathophysiology of STDT abnormalities. Methods STDT was investigated in fifteen PD patients who underwent real and sham cerebellar continuous theta burst stimulation (cTBS) in the OFF condition. Eight patients underwent a further real cTBS session in ON condition. STDT was measured on both hands before, 5 and 25 min after real and sham cTBS delivered over the cerebellar hemisphere ipsilateral to the more affected side. We controlled the efficacy of our protocol by monitoring primary motor cortex (M1) excitability. Ten healthy subjects acted as control group. Results STDT values were increased in PD patients in the OFF condition compared with healthy subjects and PD patients in the ON condition. In PD patients OFF condition, real but not sham cerebellar cTBS, significantly reduced STDT values only in the hand ipsilateral to the stimulated cerebellar hemisphere. Cerebellar cTBS also decreased motor evoked potentials (MEP) size in the contralateral M1. When PD patients were tested in the ON condition, cerebellar cTBS failed to modify STDT values. Conclusion cerebellar cTBS improved STDT values in PD patients exclusively in OFF condition. We hypothesize that cerebellar stimulation partially compensates for increased STDT values only when patients are OFF dopaminergic therapy. This suggests that the cerebellum may act as compensatory system in PD.